The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms24065093
|View full text |Cite
|
Sign up to set email alerts
|

Uridine Alleviates Sepsis-Induced Acute Lung Injury by Inhibiting Ferroptosis of Macrophage

Abstract: Uridine metabolism is extensively reported to be involved in combating oxidative stress. Redox-imbalance-mediated ferroptosis plays a pivotal role in sepsis-induced acute lung injury (ALI). This study aims to explore the role of uridine metabolism in sepsis-induced ALI and the regulatory mechanism of uridine in ferroptosis. The Gene Expression Omnibus (GEO) datasets including lung tissues in lipopolysaccharides (LPS) -induced ALI model or human blood sample of sepsis were collected. In vivo and vitro, LPS was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 50 publications
(56 reference statements)
1
11
0
Order By: Relevance
“…Our data also demonstrated that the level of ferroptosis in CD68 + macrophages (or the number of CD68 + -4-HNE + macrophages/field) was decreased by administration of the Piezo1 inhibitor (GsMTx4), followed by a decline in the number of M1-like macrophages and improved lung injury in experimental MA-ALI mice. Our finding was similar to those of other previous reports, where uridine alleviated sepsis-induced acute lung injury by inhibiting ferroptosis of macrophages [ 52 ]; activated ferroptosis in macrophages contrarily accelerated the occurrence of sepsis [ 53 ]. Moreover, a previous study demonstrated that ferroptosis was triggered by increasing M1-like macrophages in neutrophilic airway inflammation, whereas quercetin decreased the level of ferroptosis in lung tissues by suppressing the pro-inflammatory M1-like macrophages [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our data also demonstrated that the level of ferroptosis in CD68 + macrophages (or the number of CD68 + -4-HNE + macrophages/field) was decreased by administration of the Piezo1 inhibitor (GsMTx4), followed by a decline in the number of M1-like macrophages and improved lung injury in experimental MA-ALI mice. Our finding was similar to those of other previous reports, where uridine alleviated sepsis-induced acute lung injury by inhibiting ferroptosis of macrophages [ 52 ]; activated ferroptosis in macrophages contrarily accelerated the occurrence of sepsis [ 53 ]. Moreover, a previous study demonstrated that ferroptosis was triggered by increasing M1-like macrophages in neutrophilic airway inflammation, whereas quercetin decreased the level of ferroptosis in lung tissues by suppressing the pro-inflammatory M1-like macrophages [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is suggested that uridine-mediated thermoregulation is through its degradation products. Uridine phosphorylase 1 (UPase1), a key enzyme in uridine degradation, is expressed in multiple organs and tissues ( Wang et al, 2020 ; Gonçalves da Silva et al, 2021 ; Lai et al, 2023 ). Inhibition of Upase1 prevents the temperature change by uridine in rabbits and rodents ( Le et al, 2013 ).…”
Section: Uridine In the Regulation Of Body Temperature And Circadian ...mentioning
confidence: 99%
“…The circadian rhythm of rodents is not consistent with that of humans, but it still has guiding significance for the application of uridine in humans. Another study suggests that daytime uridine supplementation inhibits lipid synthesis, reduces polyunsaturated fatty acid synthesis and increases the proportion of saturated fatty acids by inhibiting the expression of Acyl-CoA synthetase long-chain family member 4 (ACSL4) ( Lai et al, 2023 ), an enzyme is known associated with obesity and fatty liver ( Zhang et al, 2018 ). Thus, it is critical to choose right time for uridine supplementation (such as when uridine phosphorylase activity is low) to achieve better therapeutic outcomes.…”
Section: Uridine In the Regulation Of Body Temperature And Circadian ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ferroptosis exists not only in alveolar epithelial cells, but also in alveolar capillary endothelial cells and macrophages (114-117). Researchers are inclined to investigate targeted drugs that can effectively inhibit the process of ferroptosis, thereby potentially impeding the progression of sepsis-induced ARDS (117)(118)(119)(120). In addition, autophagy also plays a role in the process of sepsis-induced lung injury.…”
Section: Cell Deathmentioning
confidence: 99%